Rate and Extent of Carbon Dioxide Uptake In Room Temperature Ionic Liquids: A New Approach Using Microdisc Electrode Voltammetry - Li, P; Henstridge, M; Xiong, L; Compton, R (2013)
A simple method is introduced which enables the simultaneous determination of both the maximum CO2 concentration and kinetics of CO2 uptake and release by a room temperature ionic liquid. This method is based upon the analysis of chronoamperometry recorded in bulk ionic liquid at intervals during exposure to CO2 and subsequent exposure to vacuum to remove the dissolved CO2. Comparing experimental data with a numerical model reveals the rate-limiting factors for both uptake and release of CO2. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.